Numerical Values for the Environmental Factors’ Influence on Surgeons’ Technical Performance Decrement: Spherical Fuzzy-SWARA Approach - Khalil Taherzadeh Chenani; Somayeh Bolghanabadi; Zahra Zamanian; Mohammad Hashemi (Journal of Health Sciences and Surveillance System)
Background: Surgical practices are critical activities within healthcare systems, and when human error (HE) occurs, the consequences can be irreparable. However, the literature on HE quantification reveals significant gaps in both structural and methodological approaches. This study aimed to suggest a new taxonomy of environmental influencing factors (EIFs) that impact surgeons’ technical performance.Methods: In this cross-sectional study, EIFs related to the operating room were selected by reviewing various literature. Structured expert judgment elicitation was used to validate the EIFs under consideration. The weight and negative impact rate of the EIFs during surgical processes on surgeons were quantified using the spherical fuzzy-SWARA (Step-wise Weight Assessment Ratio Analysis) method and an elevenpoint numerical scale, respectively. Questionnaires from expert surgeons were employed to quantify the weight and negative impact rate of the EIFs.Results: The taxonomy of nine EIFs was validated through individual interviews with surgeons from three regional hospitals. The ranking of the influence of EIFs showed some conflicts regarding weight and negative impact rate. Specifically, climate conditions and music received the highest and lowest grades in both weight and negative impact rates.Conclusion: The current study offers an original contribution to developing a new taxonomy based on domain-specific knowledge. The proposed EIFs taxonomy illustrates how surgeons’ reliability can be degraded qualitatively and quantitatively. Furthermore, the results could enhance patient safety programs in the operating room.